Structure of dystrophia myotonica protein kinase. - Elkins, J; Amos, A; Niesen, F; Pike, A; Fedorov, O; Knapp, S (2009)
Dystrophia myotonica protein kinase (DMPK) is a serine/threonine kinase composed of a kinase domain and a coiled-coil domain involved in the multimerization. The crystal structure of the kinase domain of DMPK bound to the inhibitor bisindolylmaleimide VIII (BIM-8) revealed a dimeric enzyme associated by a conserved dimerization domain. The affinity of dimerisation suggested that the kinase domain alone is insufficient for dimerisation in vivo and that the coiled-coil domains are required for stable dimer formation. The kinase domain is in an active conformation, with a fully-ordered and correctly positioned alphaC helix, and catalytic residues in a conformation competent for catalysis. The conserved hydrophobic motif at the C-terminal extension of the kinase domain is bound to the N-terminal lobe of the kinase domain, despite being unphosphorylated. Differences in the arrangement of the C-terminal extension compared to the closely related Rho-associated kinases include an altered PXXP motif, a different conformation and binding arrangement for the turn motif, and a different location for the conserved NFD motif. The BIM-8 inhibitor occupies the ATP site and has similar binding mode as observed in PDK1.